Atala Butterfly, Atala Hairstreak, Coontie Hairstreak, Eumaeus atala Poey 1832 (Insecta: Lepidoptera: Lycaenidae) - Sandy Koi; Donald W. Hall (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This revised 11-page fact sheet that discusses the Atala butterfly was written by Sandy Koi and Donald W. Hall, and published by the UF Entomology and Nematology Department, March 2016.